Risk Identification Analysis of Management of State-Owned Goods (Case Study of ABC Work Unit) - Anggraini, Debura Nila; Setyaningrum, Dyah (E-Jurnal Akuntansi, 2024)
The management of State-Owned Assets (SOA) at the ABC Office has consistently been identified as an issue in the audit findings of the Supreme Audit Agency (BPK) from 2021 to 2023. This persistent concern necessitates an analysis to determine whether the risk identification processes for SOA management at the ABC Office align with the standards outlined in PMK Number 222 of 2021 and KMK Number 105 of 2022. This study employs a qualitative case study methodology. The research findings were derived from a content analysis of secondary data and validated through semi-structured interviews with eight informants employed at the ABC Office. These combined methods ensured the reliability and depth of the results. The study's findings reveal that the risk identification process for managing State-Owned Assets does not fully comply with the relevant regulations. A significant issue lies in the tendency to prioritize risk events based on the focus and directives of the unit leader overseeing the risk owner. Consequently, several critical risks related to SOA management remain unidentified. To address these shortcomings, it is essential for the ABC Office to enhance the involvement of the risk management unit. By providing greater support to the SOA management unit (the risk owner), the risk management unit can facilitate the selection of appropriate risk identification techniques. This approach would enable the identification of key risks that hinder effective SOA management, thereby improving compliance and operational effectiveness.